Efficient Carrier Confinement in AlGaN‐Based Deep‐Ultraviolet Light‐Emitting Diodes with a Composition‐Graded Electron‐Blocking Layer. Issue 2 (23rd December 2022) - Ye, Wei-Te; Cheng, Zai-Jun; Ren, Zhi-Yu; Li, Chen; Zheng, Jin-Jian; Gao, Mo-Ran; Cai, Li-E; Yang, Yu-Lin
Abstract : The serious electron leakage and poor transport of hole injection layers in deep‐ultraviolet (DUV) light‐emitting diodes (LEDs) lead to an imbalance between the hole and electron currents, which reduces the device's performance. Herein, a new DUV LED structure is designed. The aluminum composition of the p‐type electron‐blocking layer (p‐EBL) gradually decreases from 0.95 to 0.75 along the growth direction, replacing the traditional bulk p‐EBL. When the injection current is 100 mA, the optical power of this structure is about 32% higher than that of the traditional structure. In addition, when the p‐EBL adopts the opposite gradient (the Al composition gradually increases from 0.75 to 0.95), the device performance suddenly drops dramatically. The related devices are simulated by Silvaco TCAD software. The results show that the performance outputs of the two opposite aluminum gradient growth modes are completely opposite. The proposed p‐EBL with a gradual step‐down Al composition along the growth direction helps to improve the efficiency of hole injection into multiple quantum wells (MQWs) and reduce the level of electron leakage. This work provides an effective solution for increasing the light output power of high‐performance DUV LEDs. Abstract : Herein, the Al composition of the p‐type electron‐blocking layer (p‐EBL) of DUV LED gradually decreases from 0.95 to 0.75 along the growth direction. When the injection current is 100 mA, the optical power of this structure is about 32% higher than that of the traditional structure. When the p‐EBL adopts the opposite gradient, the device performance suddenly drops dramatically.